USE OF LIGNO-CELLULOSE RESIDUES IN THE ELABORATION OF ECOLOGICAL SECONDARY PACKAGES - Tamayo Gutiérrez, Evelin (2017)
The present study proposes an alternative to the use of petroleum materials and vegetal lignocellulosic forest materials to manufacture of secondary packages. Boxes were made with fibers obtained from banana and coconut, agglutinated with rice. Firstly, it was evaluate the amount of water soluble solids was evaluated in the stream, a characteristic that showed significant differences, and of starch, where there were no statistical differences. Subsequently, agglomerates of the rice variety INIAP 15 and the vegetal fibers were elaborated in two different percentages of composition for each type of fiber. Where there were evaluate of density, tension and resistance. Coconut-fiber and banana-based agglomerates reached the highest values in the three physical characteristics evaluated, unlike the agglomerate made from sugarcane, which was eventually discarded as an alternative material in the manufacture of boxes.